Visual morphometry and three non-invasive markers in the evaluation of liver fibrosis in chronic liver disease. (2nd January 2017) - Agrawal, Swastik; Hoad, Caroline L.; Francis, Susan T.; Guha, Indra N.; Kaye, Philip; Aithal, Guruprasad P.
Abstract: Objective: Liver fibrosis is traditionally graded into categorical stages with cirrhosis as the highest stage. However, cirrhosis stage may vary between individuals widely in terms of the amount of fibrosis which is not assessed by traditional staging systems. We aimed to utilise visual morphometry to quantify the amount of fibrosis in liver biopsy and compare how non-invasive methods of quantifying liver fibrosis correlated with histological measures. Materials and methods: Liver biopsy specimens from 115 consecutive chronic liver disease patients were assessed by a single pathologist for fibrosis stage by the Clinical Research Network and METAVIR systems as well as percentage fibrosis by visual morphometry. Liver T 1 relaxation times, liver stiffness measurement (LSM) by transient elastography and enhanced liver fibrosis (ELF) score were compared between fibrosis stages. In addition, these parameters were correlated with pathologist's visual estimate of percentage fibrosis and their predictive ability for advanced fibrosis and cirrhosis assessed by area under receiver operating curve (AUROC). Results: All four parameters increased sequentially from fibrosis stage F0 to F4 ( p <.001 for each). AUROCs for advanced fibrosis and cirrhosis were 0.931 and 1.000 respectively for pathologist's estimate of fibrosis, 0.707 and 0.926 for ELF score, 0.763 and 0.972 for T 1 and 0.881 and 0.989 for LSM. LSM, ELF score and T 1 correlated significantly with pathologist's estimate of percentage fibrosis. Conclusion: Non-invasive markers of fibrosis LSM, ELF and T 1 relaxation time provide continuous surrogates for categorical histopathological staging of fibrosis which can be useful as markers of progression and regression of fibrosis on follow-up.